TRATAMENTO BIOLÓGICO DE ESGOTO SANITÁRIO COMPOSTO POR REATOR ANAERÓBIO DE LEITO FLUIDIZADO E FILTRO PERCOLADOR COM INSERÇÃO DE UMA ETAPA INTERMEDIÁRIA DE AERAÇÃO - Machado Filho, José Geraldo (2015)
Bad smell originated from the sewage biological treatment results in disturbance to the communities situated around these stations and is harmful to the operators’ health. This study presents results obtained from the monitoring of a sewage station treatment aiming to reduce the organic load and total suspended solids from the final effluent as well as the bad smell caused mainly by the hydrogen sulfide. The system comprised a Upflow Anaerobic Sludge Blanked (UASB), a percolator biological filter and secondary decanter. The study was divided into five phases and operated for 271 days. Phase 1 was composed of anaerobic reactor, aeration tank, percolator biological filter and secondary decanter; phase 2 had anaerobic reactor, aeration tank, percolator biological filter, secondary decanter and sludge recirculation; phase 3 had anaerobic reactor, aeration tank, secondary decanter and mud recirculation; phase 4 was composed of anaerobic reactor, aeration tank, percolator biological filter, secondary decanter, mud recirculation and final effluent recirculation, and phase 5 comprised anaerobic reactor, aeration tank with polyurethane foam, percolator biological filter, secondary decanter, mud recirculation and final effluent recirculation. All phases presented efficacy to remove oxygen chemical demand and oxygen biochemical demand ranging from 81 to 94% and total suspended solids from 71 to 92%. The sulfide removal, in the form of hydrogen sulfide in aqueous medium in the aeration tank presented 44,7% efficacy, the aeration tank release of sulphydric gas presented 70% reduction and up to 95% reduction of hydrogen sulfide in the air measured in the station area. The innovation in this operational system of treatment was the development of an aeration system, situated between the anaerobic reactor and the percolator biological filter, comprising a compressor with 1,132.7 L.min-1 air flow maximum capacity and ten fine microbubble plate diffusers, with 152.0 mm diameter and 0.5 to 1.5 mm porosity, installed 1m deep, inside the aeration tank, with a 15.0 cm distance between them, 300 L.min-1 total air flow and keeping the average dissolved oxygen concentration in the tank from 0.5 to 5.3 mg.L-1.